2011
DOI: 10.1002/ddr.20486
|View full text |Cite
|
Sign up to set email alerts
|

Potential for phosphodiesterase inhibitors in the management of autoimmune diseases

Abstract: Phosphodiesterases (PDEs) and their substrates, cAMP and cGMP, are ubiquitously expressed in the immune system. Inhibiting PDEs may represent a novel approach for regulating immune functions and have a therapeutic potential in the management of autoimmune diseases. Phosphodiesterase inhibitors (PDEi) have proved effective in clinical trials in the management of pulmonary artery hypertension and Raynaud's phenomenon. Data from animal models suggest that the immunomodulatory effect of PDEi may have a therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Studies showed that tadalafil significantly decreased symptoms including frequency, and duration of attacks (Roustit et al, 2013). In animal models, tadalafil proved efficacy in alleviating symptoms of osteoarthritis, a mechanism that involved reduction of cell influx and Tumor necrosis factor (TNF) release (Shenoy, Agarwal, Agarwal, Misra, & Naik, 2011).…”
Section: Tadalafil In Autoimmune Diseasementioning
confidence: 99%
“…Studies showed that tadalafil significantly decreased symptoms including frequency, and duration of attacks (Roustit et al, 2013). In animal models, tadalafil proved efficacy in alleviating symptoms of osteoarthritis, a mechanism that involved reduction of cell influx and Tumor necrosis factor (TNF) release (Shenoy, Agarwal, Agarwal, Misra, & Naik, 2011).…”
Section: Tadalafil In Autoimmune Diseasementioning
confidence: 99%
“…50 Manifestations of systemic sclerosis include Raynaud's phenomenon, lung fibrosis, and pulmonary artery hypertension (PAH). 51 An immune response is generated by antigens in these patients. T-cells are activated early in the disease process, and these, along with other inflammatory cells such as macrophages, monocytes, mast cells, and eosinophils, infiltrate tissues.…”
Section: Pde Inhibitors In Autoimmune Disease Systemic Sclerosis (Sclmentioning
confidence: 99%